ANALYSIS OF THE EXISTING CONDITION ON PARKING BUILDING AT SULTAN HASANUDDIN INTERNATIONAL AIRPORT - Rachim, Yunus; Chaerul, Muhammad; Gusty, Sri (ASTONJADRO, 2021)
The existing parking area at Sultan Hasanuddin Airport Makassar has 675 four-wheel parking areas, which cannot accommodate about 10 million passengers in 2013 and every year there is an increase. This study aims to analyze the characteristics of parking, especially the handling of four-wheeled vehicles in the parking building from entry, dropout, pickup, maneuver, clearance, vehicle rotation and parking slots to exiting the building. Analyze the parking area related to the level of safety and ease of use of parking buildings, especially on the semi-basement floor at Sultan Hasanuddin Airport. The method used for this research is a qualitative method, namely research that is descriptive and tends to use analysis from the data that has been collected and direct observation on the existing parking building at Sultan Hasanuddin Airport Makassar. The data collection process was carried out in two stages, namely the preliminary survey and the main survey. The results of research and observations of the existing parking building at Sultan Hasanuddin Airport, especially on the basement floor, show that the construction of a parking building that was built in terms of size, height clearance, slope, parking space layout, facilities are in accordance with the minimum standard of parking buildings, but there are some works such as sidewalks. and a stopper whose placement reduces the parking area and vehicle circulation.